Between sea, mountain and iris around the world: an approach to the Ushuaia Prison Museum - Negretti, Natalia (GIS - Gesture, Image and Sound - Anthropology Journal, 2020)
“Los invitamos a caminar por los pasillos estrechos, asomarse a las celdas para imaginar cómo habría sido la vida en la cárcel”. This is an invitation to Ushuaia Museo Prison (Argentina) on its website. Inaugurated in 1902 and transferred from San Juan del Salvamento’s military prison, Ushuaia’s prison has a long trajectory. It is currently part of a historical, cultural, and tourist arena in the city just for being a museum. Documentaries and books in Argentina as well as their characteristics imply a certain correlation between tourism and this place. Coming from an old trial prison to become a museological and tourist place, it revitalizes memory. What were the necessary arrangements for such change? This article presents a correlation between two main events: the deactivation of the prison and the new function as a museum.